BACTERICIDAL ACTIVITY OF ETHANOLIC LEAF EXTRACT AND LEAF ESSENTIAL OIL OF Rosmarinus officinalis L. ON SOME FOODBORNE BACTERIA - CASTAÑO P, Hader I.; CIRO G., Gelmy; ZAPATA M., José E.; JIMÉNEZ R., Silvia L. (Vitae, 2010)
This work evaluated the bactericidal activity and determinated the Minimum Inhibitory Concentration (MIC) of ethanolic extract and essential oil from Rosmarinus officinalis L. leaves on microorganisms of interest in food industry: Escherichia coli, Staphylococcus aureus, Salmonella typhimurium, Shigella sonnei, Listeria monocytogenes, Pseudomonas aeruginosa, Bacillus cereus and Lactobacillus plantarum. The essential oil showed a broad spectrum of antimicrobial action for both Gram positive and Gram negative bacteria with MICs between 512 - 4096 ppm. The ethanolic extract showed antimicrobial activity against S. sonnei, S. typhimurium and L. monocytogenes with a MIC of 1024 ppm. Nisin was used as positive control and showed a strong growth inhibition of all bacteria tested with MICs between 2 and 1024 ppm. Our result shows that preservatives commonly used in the food industry have lower antimicrobial activity than those found in essential oil from R. officinalis L. leaves.